1991
DOI: 10.1017/s0950268800056521
|View full text |Cite
|
Sign up to set email alerts
|

Listeria faecal carriage by renal transplant recipients, haemodialysis patients and patients in general practice: its relation to season, drug therapy, foreign travel, animal exposure and diet

Abstract: SUMMARYAbout 2 3 % (16/700) of faecal specimens from renal transplant recipients and patients having home haemodialysis as well as patients attending their general practitioners with symptoms of gastroenteritis yielded Listeria species 40% of positive faeces contained more than one Listeria species or serovar. The proportion of positive specimens was similar in all three patient groups. Listeria were isolated from 5-6 % (10/177) of renal transplant recipients on one or more occasions over the period of a year.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 21 publications
4
18
0
Order By: Relevance
“…Using repeated sampling, Listeria can be detected in the feces of nearly 70% of healthy nonpregnant individuals and 44% of pregnant women [21, 31]. MacGowan et al found that Listeria was isolated from 5.6% (10/177) of renal transplant recipients on 1 or more occasions over the period of a year; moreover, >1 species or serovar of listeria can be isolated from 40% of fecal carriers, and no cases of clinical infection occurred in any fecal carriers [33]. Fecal, cervicovaginal, and oropharyngeal carriage of L. monocytogenes has been reported as a possible predisposing factor for perinatal listeriosis [34, 35].…”
Section: Discussionmentioning
confidence: 99%
“…Using repeated sampling, Listeria can be detected in the feces of nearly 70% of healthy nonpregnant individuals and 44% of pregnant women [21, 31]. MacGowan et al found that Listeria was isolated from 5.6% (10/177) of renal transplant recipients on 1 or more occasions over the period of a year; moreover, >1 species or serovar of listeria can be isolated from 40% of fecal carriers, and no cases of clinical infection occurred in any fecal carriers [33]. Fecal, cervicovaginal, and oropharyngeal carriage of L. monocytogenes has been reported as a possible predisposing factor for perinatal listeriosis [34, 35].…”
Section: Discussionmentioning
confidence: 99%
“…Using this bacterium to investigate the underlying pathogenesis of prenatal infection is clearly important given the ubiquitous presence of this pathogen in our food supply, colonization within the gastrointestinal tract, propensity for disseminated infection during pregnancy, and alarming rate of morbidity and mortality associated with human prenatal infection (Gellin and Broome 1989, Iida, et al 1998, MacGowan, et al 1991, Mylonakis, et al 2002, Silver 1998, Southwick and Purich 1996). Here, a somewhat surprising degree of resistance to L. monocytogenes infection for placental cells has been described using human organ cultures (Abrahams, et al 2006, Koga and Mor 2008, Robbins and Bakardjiev 2012).…”
Section: Infection Induced Shifts In Treg Suppression and Pregnancy Cmentioning
confidence: 99%
“…Nevertheless, Lm can be shed asymptomatically, persist in human and animal feces and be released in the environment [15], [16]. Lm is a ubiquitous bacterium that also thrives in diverse external environments such as soil, water, decaying plants, and silage, exposing wild animals and cattle to multiple opportunities of ingestion and perpetuating Lm transmission [17].…”
Section: Introductionmentioning
confidence: 99%